An Ordinance to regulate the government of parks and other public pleasure grounds of The City of New York, at 600, § XXIV (1903) - (:unkn) unknown (General Publisher, 1903)
No one shall fire or carry any firearm, fire cracker, torpedo or fire-works, nor make a fire, nor make any oration, nor conduct any religious or other meeting or ceremony within any of the parks, parkways, squares or places in The City of New York under the jurisdiction of the Department of Parks without special permission from the Commissioner having jurisdiction
--
Keywords: DISCHARGE; CARRY - CERTAIN PUBLIC PLACES